FAT4 identified as a potential modifier of orofacial cleft laterality. Issue 7 (15th June 2021) - Curtis, Sarah W.; Chang, Daniel; Sun, Miranda R.; Epstein, Michael P.; Murray, Jeffrey C.; Feingold, Eleanor; Beaty, Terri H.; Weinberg, Seth M.; Marazita, Mary L.; Lipinski, Robert J.; Carlson, Jenna C.; Leslie, Elizabeth J.
Abstract: Orofacial clefts (OFCs) are common (1 in 700 births) congenital malformations that include a cleft lip (CL) and cleft lip and palate (CLP). These OFC subtypes are also heterogeneous themselves, with the CL occurring on the left, right, or both sides of the upper lip. Unilateral CL and CLP have a 2:1 bias towards left‐sided clefts, suggesting a nonrandom process. Here, we performed a study of left‐ and right‐sided clefts within the CL and CLP subtypes to better understand the genetic factors controlling cleft laterality. We conducted genome‐wide modifier analyses by comparing cases that had right unilateral CL (RCL; N  = 130), left unilateral CL (LCL; N  = 216), right unilateral CLP (RCLP; N  = 416), or left unilateral CLP (LCLP; N  = 638), and identified a candidate region on 4q28, 400 kb downstream from FAT4, that approached genome‐wide significance for LCL versus RCL ( p  = 8.4 × 10 −8 ). Consistent with its potential involvement as a genetic modifier of CL, we found that Fat4 exhibits a specific domain of expression in the mesenchyme of the medial nasal processes that form the median upper lip. Overall, these results suggest that the epidemiological similarities in left‐ to right‐sided clefts in CL and CLP are not reflected in the genetic association results.